The bread of the strong : Lacouturisme and the folly of the Cross, 1910-1985 - Downey, Jack Lee (Catholic practice in North America., 2015)
"The Bread of the Strong investigates the origins, development, and migration of a Roman Catholic retreat movement founded by Onesime Lacouture, SJ. Although suppressed in its original host region of Quebec, it migrated to the United States, thanks largely to John Hugo's advocacy, and critically influenced Dorothy Day's spiritual development"--